INVESTMENT RISK IDENTIFICATION FOR THREE STARS HOTEL IN BALI - I Gusti Agung Adnyana Putera; Wayan Sri Kristinayanti; I Nyoman Norken (Jurnal Teknobisnis, 2012)
The three stars hotel occupation in Bali is unpredictable compared to other luxury hotels. However the average length of stay at the hotel of this level is higher than the other five-star hotel. Both types provide opportunities and risk to investor, thus, that investor need to conduct broad examination before do some investment, especially to identify risk factors for investment. This paper presents comprehensive risk factors of investing in three star hotels in Bali. Data obtained from structured interview to the tourist of the various levels of tourism management in Bali. The data ware processed using a descriptive qualitative into three major groups namely the major risk, unacceptable risk, and undesirable risk. The results of this study indicate that there ware 40 types of investment risk on a three-star hotel in Bali. Amongst the 40 types of these risk, only 25% was acceptable risk and negligible risk, while the rest categorized major risk. Between the major risk, 50% was unacceptable risk and the remaining 25% was an undesirable risk. Unacceptable risk were classified into risk occurs more often in pre-design activities which mainly related to marketing activity, even as the dominant risk was the environmental problem, especially with the traditional village-awing awing (local village regulations). Risks a classified as undesirable risk were more common in the activities during the operation of hotels, which are generally triggered from the human risk.